2021
DOI: 10.1016/j.scitotenv.2020.142324
|View full text |Cite
|
Sign up to set email alerts
|

Repeated exposure of Caco-2 versus Caco-2/HT29-MTX intestinal cell models to (nano)silver in vitro: Comparison of two commercially available colloidal silver products

Abstract: Colloidal silver products are sold for a wide range of disinfectant and health applications. This has increased the potential for human exposure to silver nanoparticles (AgNPs) and ions (Ag + ), for which oral ingestion is considered to be a major route of exposure. Our objective was to evaluate and compare the toxicity of two commercially available colloidal silver products on two human intestinal epithelial models under realistic exposure conditions.Mesosilver™ and AgC were characterized and a concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 62 publications
1
20
0
Order By: Relevance
“…To date, only milk oligosaccharides [ 38 , 39 ] and soluble plantain fibers at a dose of 5 g·L −1 [ 18 ] have shown the ability to reduce the adhesion of human ETEC strains (others than H10407) to a Caco-2 cell line. Here, we used a co-culture of enterocytes and mucus-secreting cells to more accurately mimic the physiological situation in the human intestine [ 42 , 98 , 99 ]. We first observed the inhibition of ETEC adhesion by both fiber-containing products on mucin beads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only milk oligosaccharides [ 38 , 39 ] and soluble plantain fibers at a dose of 5 g·L −1 [ 18 ] have shown the ability to reduce the adhesion of human ETEC strains (others than H10407) to a Caco-2 cell line. Here, we used a co-culture of enterocytes and mucus-secreting cells to more accurately mimic the physiological situation in the human intestine [ 42 , 98 , 99 ]. We first observed the inhibition of ETEC adhesion by both fiber-containing products on mucin beads.…”
Section: Discussionmentioning
confidence: 99%
“…Caco-2 and HT29-MTX cells were cultivated as already reported [ 19 ]. The Caco-2/HT29-MTX co-culture (ratio 70:30) was maintained for 18 days to reach the full differentiation stage [ 42 ]. Cells were pre-treated or not with fiber-containing products (2 g·L −1 ) for a 3 h period.…”
Section: Methodsmentioning
confidence: 99%
“…Second, to integrate the host part, we used cellular-adhesion experiments with the Caco-2/HT29-MTX cellular co-culture model. This model includes Caco-2 enterocytes-like cells and HT29-MTX cells secreting mucus polysaccharides [59][60][61]. To date, only milk oligosaccharides [27,29] and soluble plantain fibers at a dose of 5 g•L −1 [28] have shown efficiency to reduce adhesion of human ETEC strains other than H10407 to the Caco-2 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…24,26−29 The application fields covered by investigations using SIMS on the HIM range from thin-film studies, 30 battery research, and optoelectronic devices characterization, 25,31 to solar cell materials 32 or steel investigations, 33 to geological and biological relevant topics. 25,34,35 A most recent review summarizes the applications of HIM−SIMS. 36 On the other hand, as the GFIS has the ability to create the light element He + beam, scanning transmission ion microscopy (STIM) can be explored on the HIM.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this way, it is possible to perform SIMS analysis of surfaces with excellent detection sensitivity, a high dynamic range (signal variations over several orders of magnitude are detectable), and differentiating the various isotopes . It has been demonstrated that SIMS on the HIM can be performed with sub-20 nm lateral resolution, which gives outstanding results in that respect compared to standalone SIMS tools. , The application fields covered by investigations using SIMS on the HIM range from thin-film studies, battery research, and optoelectronic devices characterization, , to solar cell materials or steel investigations, to geological and biological relevant topics. ,, A most recent review summarizes the applications of HIM–SIMS …”
Section: Introductionmentioning
confidence: 99%